Evaluating the Cognitive Impacts of Drospirenone, a Spironolactone-Derived Progestin, Independently and in Combination With Ethinyl Estradiol in Ovariectomized Adult Rats - Koebele, Stephanie V.; Poisson, Mallori L.; Palmer, Justin M.; Berns-Leone, Claire; Northup-Smith, Steven N.; Peña, Veronica L.; Strouse, Isabel M.; Bulen, Haidyn L.; Patel, Shruti; Croft, Corissa; Bimonte-Nelson, Heather A. (Frontiers in Neuroscience, 2022)
Oral contraceptives and hormone therapies require a progestogen component to prevent ovulation, curtail uterine hyperplasia, and reduce gynecological cancer risk. Diverse classes of synthetic progestogens, called progestins, are used as natural progesterone alternatives due to progesterone’s low oral bioavailability. Progesterone and several synthetic analogs can negatively impact cognition and reverse some neuroprotective estrogen effects. Here, we investigate drospirenone, a spironolactone-derived progestin, which has unique pharmacological properties compared to other clinically-available progestins and natural progesterone, for its impact on spatial memory, anxiety-like behavior, and brain regions crucial to these cognitive tasks. Experiment 1 assessed three drospirenone doses in young adult, ovariectomized rats, and found that a moderate drospirenone dose benefited spatial memory. Experiment 2 investigated this moderate drospirenone dose with and without concomitant ethinyl estradiol (EE) treatment, the most common synthetic estrogen in oral contraceptives. Results demonstrate that the addition of EE to drospirenone administration reversed the beneficial working memory effects of drospirenone. The hippocampus, entorhinal cortex, and perirhinal cortex were then probed for proteins known to elicit estrogen- and progestin- mediated effects on learning and memory, including glutamate decarboxylase (GAD)65, GAD67, and insulin-like growth factor receptor protein expression, using western blot. EE increased GAD expression in the perirhinal cortex. Taken together, results underscore the necessity to consider the distinct cognitive and neural impacts of clinically-available synthetic estrogen and progesterone analogs, and why they produce unique cognitive profiles when administered together compared to those observed when each hormone is administered separately.